Improving the usability and accessibility in aging rural communities: rural policy for innovation in an aging community - Rivers, James (Kansas State University, 2014)
Most adults have grown accustomed to the current design orientation of their communities; however, as adults grow older they will be hard pressed to maintain their current lifestyle and level of activity in their community. This research identifies the importance of incorporating accessibility and usability elements into the streetscape of a community to encourage the integration of seniors into community life. One of the four pillars of the Main Street approach is design. This encompasses the design of building facades, streetscapes, and public spaces. This research looks at the Kansas Main Street program and investigates its success in furthering usability and accessibility of streetscapes in rural communities experiencing an aging population and infrastructure. My thesis is if the Main Street organizations of Kansas were concerned about the access and use of streetscapes for elderly populations, their concern would be expressed in development plans and practices through their Main Street program undertakings. Through this research, I have found that while rural communities see the value in accessible streetscapes their primary barrier to creating them is a financial one.
Keywords: Mainstreet; Universal Design; Urban Planning (0999)